Practical shooting sport in Russian sport system: essential specifications and features - Kondrukh, A. I. (Theory and Practice of Physical Culture, 2017)
In the context of the ongoing discussion on the notion of sports on the whole and sport classification criteria in particular, we consider herein some essential specifications that make practical shooting a special shooting sport discipline including: highly variable competitive settings plus many factors of influence on the shooting process (targets placed at different distances and variable in sets, groups, relative positions etc. that are never the same in every competition; shooting positions are always changed in competitions; settings of the shooting positions are varied in competitions; scoring shots may come to 1000; the numbers of targets normally vary around 600-700; different weather conditions; and various technical and ballistic characteristics of the guns); potent fire arms are used in the shooting with the shooter required to rapidly move from one position to another and change positions (prone, standing, kneeled, squatted, covered etc.); individual/ couple (duel)/ group shooting contests designed to simulate actual fire contacts with one or few opponent(s).